Urgency Of Forming Legislation About The Online Petition Perspective Good Legislation Making - Khobibah Khobibah; Nabilla Farah Quraisyta (International Journal of Law and Society, 2025)
In the era of globalization , digital communication media is developing with rapid make it easier everyone in respond and express opinion through Network online social . Change.org is one of the sites that can utilized Good individual and also group For submit A petition online against decision the perceived government not enough appropriate . Success on monitoring the decision government in Indonesia through this online petition including very good , but sadly Not yet There is regulation specifically that covers it . In line with problem said , the purpose writing article This is For analyze urgency making A Regulation legislation about Online Petitions and their preparation use perspective Good Legislation Making . Research law normative which prioritizes Conception Good Legislation Making become appropriate methodology with objective research that was initiated . For make it easier discussion , poured out formulation problem , the first How Urgency Formation Regulation Legislation About Online Petition , Second How Ideal Concept of Regulation Legislation About Perspective Online Petition Good Legislation Making. From results analysis found that in Indonesia indeed Not yet There is regulation special that becomes umbrella law online petitions as well draft idealist making legislation online petition using perspective Good Legislation Makang .